Iron phosphate materials as cathodes for lithium batteries the use of environmentally friendly iron in lithium batteries - Prosini, Pier Paolo; SpringerLink (Online service). (London Springer, 2011)
Iron Phosphate Materials as Cathodes for Lithium Batteries describes the synthesis and the chemical?physical characteristics of iron phosphates, and presents methods of making LiFePO4 a suitable cathode material for lithium-ion batteries. The author studies carbon?s ability to increase conductivity and to decrease material grain size, as well as investigating the electrochemical behaviour of the materials obtained. Iron Phosphate Materials as Cathodes for Lithium Batteries also proposes a model to explain lithium insertion/extraction in LiFePO4 and to predict voltage profiles at various discharge rates. Iron Phosphate Materials as Cathodes for Lithium Batteries is written for postgraduate students and researchers in electrochemistry, R&D professionals and experts in electrochemical storage.
1. Electrode Materials for Lithium-Ion Batteries -- 2. Triphylite -- 3. Determination of the Diffusion Coefficient of LiFePO4 -- 4. Vivianite and Beraunite -- 5. Amorphous Iron Phosphate -- 6. Nano-crystalline LiFePO4 -- 7. Long-Term Cyclability of Nano-crystalline LiFePO4 -- 8. Factors Affecting the Rate Performance of LiFePO4 -- 9. Versatile Synthesis of Carbon-Rich LiFePO4 -- 10. Modeling the Voltage Profile for LiFePO4.
Electronic reproduction.
Keywords: Electronic book; Lithium cells; Cathodes; Phosphates; Iron compounds